A STUDY TO ASSESS THE EFFECTIVENESS OF SELF-INSTRUCTIONAL MODULE ON KNOWLEDGE REGARDING HUMAN RIGHTS OF MENTALLY ILL AMONG 3RD YEAR BSC NURSING STUDENTS IN SELECTED COLLEGE OF VADODARA CITY - Mr. Dhruv Thaker; Dr. Vinil Upendra Babu (The Bioscan, 2025)
To assess the existing knowledge level of students regarding Human Rights of Mentally Ill among 3rd year B.Sc nursing students.